2017
DOI: 10.1038/aps.2017.34
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary delivery of nanoparticle chemotherapy for the treatment of lung cancers: challenges and opportunities

Abstract: Lung cancer is the second most prevalent and the deadliest among all cancer types. Chemotherapy is recommended for lung cancers to control tumor growth and to prolong patient survival. Systemic chemotherapy typically has very limited efficacy as well as severe systemic adverse effects, which are often attributed to the distribution of anticancer drugs to non-targeted sites. In contrast, inhalation routes permit the delivery of drugs directly to the lungs providing high local concentrations that may enhance the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
176
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 226 publications
(178 citation statements)
references
References 231 publications
(276 reference statements)
1
176
0
1
Order By: Relevance
“…Fe III -TA complexes on the highly porous surface of the CaCO 3 template. By repeating the TA/Fe III coating cycle, the shell thickness gradually increased to 162 ± 31 nm ((Fe III -TA) 3 ) and 207 ± 32 nm ((Fe III -TA) 6 ), as observed from the transmission electron microscopy (TEM) images (Figure 1a3-c5). This represents an average thickness of ≈20 nm after each MPN coating cycle.…”
Section: Assembly and Characterization Of Mpn Capsulesmentioning
confidence: 75%
See 2 more Smart Citations
“…Fe III -TA complexes on the highly porous surface of the CaCO 3 template. By repeating the TA/Fe III coating cycle, the shell thickness gradually increased to 162 ± 31 nm ((Fe III -TA) 3 ) and 207 ± 32 nm ((Fe III -TA) 6 ), as observed from the transmission electron microscopy (TEM) images (Figure 1a3-c5). This represents an average thickness of ≈20 nm after each MPN coating cycle.…”
Section: Assembly and Characterization Of Mpn Capsulesmentioning
confidence: 75%
“…The presence of Fe in the capsules and the complete removal of CaCO 3 and EDTA were confirmed by X-ray photoelectron spectroscopy ( Figure S2, Supporting Information). The shell thickness of the capsules after one TA/Fe III coating cycle (denoted as (Fe III -TA) 1 ), was 108 ± 30 nm, which is thicker than typical Fe III -TA films (10 nm) [19a,23] owing to the adsorption of the Scheme 1. a) Preparation of (Fe III -TA) 1 , (Fe III -TA) 3 , and (Fe III -TA) 6 capsules with different shell thicknesses, achieved by repeating the MPN coating cycle; the index n in (Fe III -TA) n denotes the number of MPN coating cycles performed. b) Fe III -TA capsule suspensions are aerosolized by an air jet nebulizer and subsequently drawn into the next generation impactor (NGI) to assess airway deposition of the MPN aerosols based on their aerodynamic behavior.…”
Section: Assembly and Characterization Of Mpn Capsulesmentioning
confidence: 99%
See 1 more Smart Citation
“…Pulmonary delivery of nanomedicines enhances lung cancer treatment by transporting encapsulated poorly water‐soluble, potent anticancer drugs directly to their intended site of action, facilitating targeted and controlled release at tumor sites and reducing the necessary dosage and mitigating off‐target side‐effects (Hitzman, Wattenberg, & Wiedmann, ; Koshkina et al, ; Tomoda et al, ); however, inhalation distributes these drugs evenly around the lungs, potentially exposing both healthy and diseased cells to chemotherapy and inducing undesirable adverse effects on the lungs (Lee, Loo, Traini, & Young, ). Drug deposition and distribution is influenced by the physical occlusion of the respiratory track by tumors, where tumors reduce the cross‐sectional area of the airway and thereby divert airflow to nonoccluded areas and reduce drug deposition on tumor tissue (Carvalho, Carvalho, & Mcconville, ; Mangal et al, ). Modeling of the effects of tumors in terms of size and location on particle transport has revealed that most drugs deposit on the frontal end of the tumor (Z. Zhang, Kleinstreuer, Kim, & Hickey, ); this alongside the heterogeneity of tumor tissues further emphasizes the advantages and necessity of nanoformulations for treating lung cancer.…”
Section: Inhalable Therapeutics For Lung Cancermentioning
confidence: 99%
“…• Noninvasive (Sung, Pulliam, & Edwards, 2007) • Dosage form easy to carry and use (Mangal, Gao, & Zhou, 2017) • Enhances treatment by localization for lung disease and avoidance off-target effects (Koshkina, Gilbert, Waldrep, Seryshev, & Knight, 1999) • Improves pharmacokinetics (Reed et al, 2013) • Reduces dosage needed (Kuzmov & Minko, 2015;Reed et al, 2013) • Lymphatic circulation can redistribute drugs into peripheral airways (Blank et al, 2013;Zarogoulidis et al, 2012) • Avoids first pass metabolism and low enzymatic activity in lungs (Greene & McElvaney, 2009;Olsson et al, 2011) • Large absorptive surface area with thin alveolar epithelium and rich blood supply for systemic disease (Breeze & Turk, 1984;Bur, Henning, Hein, Schneider, & Lehr, 2009;Edwards et al, 1997;Patton, 1996) • Possible high lung toxicity of drug (Kuzmov & Minko, 2015) • Possible degradation by macrophages (Kuzmov & Minko, 2015) • Risk of drug-induced lung injury or exacerbation of existing diseases (Card, Zeldin, Bonner, & Nestmann, 2008) • Aerosolization can potentially negatively influence active pharmaceutical ingredient activity (Beck-Broichsitter, Knuedeler, Schmehl, & Seeger, 2013;Dailey et al, 2003;Smith, 1997) • Deposition and distribution in different regions challenging and influenced by lung geometry, condition, and breathing pattern (Mangal et al, 2017) • Potential absorption into blood and lymphatic circulation (Choi et al, 2010;Seydoux et al, 2016;Tatsumura, Koyama, Tsujimoto, Kitagawa, & Kagamimori, 1993) • Delivery system can be time-consuming and/or cumbersome to use • Quick administration (i.e., injection, oral) • Immediate dissolution in bloodstream with IV injections • No extra or complicated devices for administration • Easily controlled and adjustable drug dosage • High patient compliance with injections and oral administration • Lower efficiency and accumulation in lung (Smola, Vandamme, & Sokolowski, 2008) • Potential adverse side effects to nontarget organs…”
Section: Inhalation Deliverymentioning
confidence: 99%